2010
DOI: 10.1007/s00066-010-2014-8
|View full text |Cite
|
Sign up to set email alerts
|

18F-FET-PET-Based Dose Painting by Numbers with Protons

Abstract: The presented investigation fortifies the feasibility of (18)F-FET-PET-based dose painting with protons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 36 publications
(50 reference statements)
0
5
0
2
Order By: Relevance
“…In a previous study, Grosu et al [8] observed a significant survival benefit in re- current high-grade gliomas that were reirradiated on the basis of combined MRI and amino acid PET/SPECT compared to MRI-based treatment alone. The feasibility of a FET-based dose painting could be demonstrated in our own planning study [17] and as well a study by Rickhey et al [20,21].…”
Section: Discussionmentioning
confidence: 79%
“…In a previous study, Grosu et al [8] observed a significant survival benefit in re- current high-grade gliomas that were reirradiated on the basis of combined MRI and amino acid PET/SPECT compared to MRI-based treatment alone. The feasibility of a FET-based dose painting could be demonstrated in our own planning study [17] and as well a study by Rickhey et al [20,21].…”
Section: Discussionmentioning
confidence: 79%
“…Dose reduction may be important for toxicity reduction in particle therapy as it is in brachytherapy, and a prospective randomized trial of lower-dose (50 Gy) versus standard dose (70 Gy) proton radiation for small-to-moderate sized uveal melanoma showed no differences in a 5-year local or systemic recurrence or visual acuity loss, suggesting lower dose may be acceptable moving forward (44). In the past decade or two, linear accelerator (LINAC) stereotactic RT (SRT), or SRS with either LINAC or gamma knife has been investigated for its potential as an alternative option to proton beam (46)(47)(48)(49)(50)(51)(52)(53). The initial experiences showed that SRT and SRS offer a noninvasive alternative to enucleation and brachytherapy in the management of uveal melanoma, with similar outcome to proton beam therapy (46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Definitive Rt For Ocular Melanomasmentioning
confidence: 99%
“…Der Tracer [18 F] -3,4-dihydroxyphenylalanin (F-DOPA) stellt eine nicht-proteinogene α-Aminosäure dar und kann ebenfalls in der neuroonkologischen Diagnostik eingesetzt werden [27]. Die AS-PET unterscheidet zuverlässig zwischen therapiebedingten Gewebeveränderungen und einem Gliomrezidiv [3,22,40,43], liefert entscheidende Informationen zur Planung von stereotaktischen Biopsien oder navigierten Resektionen [23,35,41] und eignet sich zur Präzisierung des Zielvolumens bei der Strahlentherapieplanung [14,32,36,44,45]. Ferner kann die FET-PET zur Beurteilung des Ansprechens eines Hirntumors auf die Therapie eingesetzt werden [36,38,39,46,48].…”
Section: Rolle Der Pet In Der Diagnostik Von Hirntumoren Im Kindes-ununclassified